Mediterranean Europe phrasebook & dictionary - Myers, Jenna (Lonely Planet, 2019)
Lonely Planet's Mediterranean Europe Phrasebook is your passport to culturally enriching travels with the most useful European phrases and vocabulary for all your travel needs. Ask for directions to the best beaches, learn about local history and culture, and navigate menus like a local- all with your trusted travel companion.